Status Keberlanjutan Program Pelepasliaran Orangutan Sumatera (Pongo abelii L.) di Bentang Alam Bukit Tiga Puluh Provinsi Jambi - Ambarita, Darmanto; Syarifuddin, Hutwan; Hamzah, Hamzah (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to analyze the sustainability status and analyze sensitive attributes (leverage analysis) on the sustainability of the Sumatran orangutan (Pongo abelii L.) reintroduction program in the Bukit Tigapuluh Landscape. The analysis was carried out using the RAPFISH method with four dimensions, namely ecological, economic, social and institutional dimensions which were then validated using the Monte Carlo method, determining the stress value and R2 value. Determining sensitive attributes is done using leverage analysis. The research results show that the sustainability status of the Sumatran Orangutan (Pongo abelii L.) reintroduction program in the Bukit Tigapuluh Landscape in the ecological and economic dimensions is quite sustainable, but in the social and institutional dimensions it is less sustainable. The results of the sensitivity analysis showed that of the total of 36 attributes used, 13 sensitive attributes were identified which influenced the sustainability index value of the Sumatran orangutan reintroduction program namely pressure on the area, number and type of nest trees, forest area area, opportunities for competition (intra and between species), level of habitat suitability, contributing to improving the community's economy, average income against UMP, potential tourist attractions, threat of habitat change, conflict management mechanisms, threat of animal hunting, level of community education and information on regulations related to management rules for Sumatran orangutans.